Maternal emotional availability and its association with maternal psychopathology, attachment style insecurity and theory of mind - Licata, Maria; Zietlow, Anna-Lena; Träuble, Birgit; Sodian, Beate; Reck, Corinna (Psychopathology, 2016)
Background/Aims:High maternal emotional availability (EA) positively affects various domains of child development. However, the question of which factors promote or hinder maternal EA has not been investigated systematically. The present study investigated several maternal characteristics, namely maternal psychopathology, maternal attachment style insecurity, and theory of mind (ToM) as possible factors that influence maternal EA. Methods: The sample was comprised of 56 mothers and their preschool-aged children. Half of the mothers were diagnosed with postpartum depression and or anxiety disorders according to DSM-IV, and the other half were healthy controls. Results: The results showed that both low maternal attachment style insecurity and high ToM skills significantly predicted maternal EA sensitivity, independently from maternal postpartum and concurrent psychopathology and education. Moreover, maternal attachment style insecurity fully mediated the link between maternal postpartum psychopathology and sensitivity. Conclusion: The findings suggest that maternal attachment style security can buffer negative effects of maternal psychopathology on maternal sensitivity in the mother-child interaction.
Gesehen am 04.06.2020